Answer:
See below
Step-by-step explanation:
We want to prove that
Taking the RHS, note
Remember that
Therefore,
Once
Then,
Hence, it is proved
You're asking for three consecutive odd numbers, then
Let, the numbers = x, x+2, x+4
It is given that, x + x+2+ x+4 = -27
3x + 6 = -27
3x = -27 - 6
x = -33/3
x = -11
Then, x+2 = -9 & x+4 = -7
In short, Your Numbers would be: -7, -9,-11
Hope this helps!
Answer:
The answer is: This statement is true :)
Step-by-step explanation:
Move down c units means minus 2 from whole function
f(x) moved down 2 units means f(x)-2
so
f(x)-2=2x²-8-2
f(x)-2=2x²-10
g(x)=2x²-10